The Review Of The Legal Aspects Of The Release Of Inpatient Medical Information In The Insurance Claims Of The BPJS At Ciremai Hospital Tingkat III 03.06.01 Cirebon City - Niar Melinda; Yani Kamasturyani; Tuti Melinda (LPPM ITEKES Mahardika, 2020)
The process of claiming health costs through BPJS requires a medical record document as one of the requirements for health cost claims, because the medical record document is confidential in releasing medical record information, the BPJS and the hospital must pay attention to the legal aspects in releasing the medical record information contained in the regulation of the minister of health of the Republic of Indonesia No. 377 of 2007. The purpose of this study was to determine the review of the legal aspects of the release of inpatient medical information in the insurance claims of the BPJS at Ciremai Hospital Tingkat III 03.06.01 Cirebon City. The method used in this research is descriptive quantitative, population this study is 1449 BPJS claim files with total of 94 BPJS claim file samples, and the method of sampling using random sampling. The result of this study are that the SOP of claiming made by Ciremai Hospital Level III 03.06.01 in Cirebon City are in accordance with legal regulations, namely Permenkes RI Number 52 of 2016 concerning Standard Health Service Rates.